Statics and Dynamics of the Language: the Issue of Balance - Гриценко, Світлана Павлівна (Київський національний університет імені Тараса Шевченка, 2018)
The vocabulary of the Ukrainian language of the XVIth–XVIIth centurу as a systemic dynamic phenomenon was studied in the thesis basing on Ukrainian-language written sources of various styles and genres, a set of techniques was selected and applied, a number of new approaches to the analysis of the time dynamics of vocabulary was proposed. It is stressed that the most noticeable are changes of vocabulary and semantics due to the verbalization of the dynamics of the culture of society – the transformations in the material-subject and production spheres, intercessions of some social and cultural dominants. It is accentuated that an important factor in the dynamics of the Ukrainian language is its interaction with the other languages, that leads to the changes in the structure of language elements, their interconnections and their functions. The correlation between dynamics and statics in the vocabulary of the Ukrainian language of the XIth–XVth century and XVIth–XVIIth century is determined, combinations of various changes of the lexical system of the Ukrainian language are characterised. Changes appear in the formation of new values of specific or borrowed lexemes as a result of metonymic transformations, semantic attraction, entering into constant phrases or cliché expressions, generalization or specialization of meanings, emergence of connotative, estimative elements of semantics. Functional reduction of the word, its absence in the written sources of the next period in comparison with the previous stage of the existence in language testifies deactualization of the notion in the language model of the world, as well as intercession of an older lexeme by a new nomination – specific or borrowed. The regularities of the expansion of the Ukrainian vocabulary due to foreign-language influences are discovered, the factors that influenced the degree of saturation of thematic and lexical-semantic groups are outlined. The architectonics of the lexical system and its conceptual organization as a reproduction of the contemporary language model of the world of Ukrainian people are revealed. The formal and semantic derivation of nominative units, adaptation of borrowings to the structure of the recipient language are analized. Dynamics of the formal structure of the vocabulary is connected with a change in the meaning of the primary lexeme. Formal derivation establishes motivational and word-formation models, outlines productive ones for the appropriate period of language development. According to the sources of the XVIth–XVIIth century both non-hybrid (monolingual) and hybrid derivatives are present there. Analysis of derivatives of foreign genesis, the history of their appearance in the Ukrainian language of the XVIth–XVIIth century, as well as the study of the functioning of borrowings in the language allowed to estimate hypothetically the place of derivation (in the source language, intermediate language, recipient language); complexity of genesis estimation of derivatives associated with the presence of common affixes and word-formation models for interacting languages. For many lexemes the time of their appearance in the Ukrainian language is specified, assumptions about time and conditions of borrowings are verified. For the study of the history of borrowings it is important to find out the history of functioning of the corresponding lexemes in the source language and intermediate languages, and their timing appearance (moment of entry), distribution and adaptation in the recipient language. Determination of the moment, the time of „birth” – appearance and rooting – of the borrowings foresees the proof of the absence of written fixation of an appropriate lexeme in older written sources. The conditional identification of the time of the first fixation and the time of borrowing allowed to find out lexemes for which the time of borrowing can be set: for such date a year / relative chronological sign, which is indicated in the written source, or exactly the year of writing a memorial are accepted. For a series of lexemes relative chronological characteristics (indication of time period from the interval of one year to another or the corresponding century) are proposed. Application of methods of determining the time of the appearance of lexeme based on the history of the designated reality contributed to the definition of borrowings that nominate the notion of material culture, the history of which is clearly established, or the time before which these borrowings could not appear in the recipient language. It was clarified that the chronology of foreign language nominatives contributes to clarification of the sources of borrowing, in particular, for alternative explanations available in science. An important role in determining the chronological characteristics of the lexemes has the information about the peculiarities of the analyzed lexemes’ functionning in the potential intermediary languages.

У статті на підставі українськомовних писемних пам’яток різних стилів і жанрів проаналізовано лексикон української мови XVI–XVII ст. як системний динамічний феномен, запропоновано низку нових підходів до аналізу динаміки лексики в часі. Виявлено фактори розвитку лексикону української мови; встановлено закономірності вербалізації позамовної сфери в окреслений період історії мови. Розкрито прояви динаміки і статики в лексиці української мови ХІ–XV ст. та XVI–XVII ст., схарактеризовано комбінаторику різних змін лексичної системи української мови. З’ясовано закономірності розширення українського лексикону завдяки деривації та іншомовним впливам, зміни архітектоніки лексичної системи та її концептуальної організації як форм відтворення тогочасної мовної картини світу українців. Досліджена формальна та семантична деривація номінативних одиниць, адаптація запозичень до структури мови-реципієнта. Звернута увага на потребі верифікації часу та умов появи в українській мові багатьох лексем.
Статика і динаміка мови: проблеми рівноваги
Keywords: dynamic; static; interaction of languages; vocabulary; specific lexeme; borrowing; source language; recipient language; intermediary language; adaptation; derivation; chronology of borrowings; динаміка; статика; взаємодія мов; лексикон; питома лексема; запозичення; мова-джерело; мова-реципієнт; мова-посередниця; адаптація; деривація; хронологія запозичування